The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12967-021-03044-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of immune cell homing gene signatures and infiltrates of lymphocyte subsets in human melanomas: discordance with CD163+ myeloid cell infiltrates

Abstract: Background Immune cells in the tumor microenvironment have prognostic value. In preclinical models, recruitment and infiltration of these cells depends on immune cell homing (ICH) genes such as chemokines, cell adhesion molecules, and integrins. We hypothesized ICH ligands CXCL9-11 and CCL2-5 would be associated with intratumoral T-cells, while CXCL13 would be more associated with B-cell infiltrates. Methods Samples of human melanoma were submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Principal component analysis (PCA) showed a clear separation between the two groups (Figure 3E). In addition, BMCs from NTN- injected mice demonstrated strong immune cell homing gene signatures 23 as shown by upregulation of Ccr4, Cxcr3, Ccl5, Cxcr5, Ccr1, Ccl2, Ccl4, and Ccr5 (Figure 3F). Moreover, we observed alterations in the gene signatures of both myeloid lineage markers and lymphoid lineage markers following NTN (Figure 3G-H).…”
Section: Resultsmentioning
confidence: 99%
“…Principal component analysis (PCA) showed a clear separation between the two groups (Figure 3E). In addition, BMCs from NTN- injected mice demonstrated strong immune cell homing gene signatures 23 as shown by upregulation of Ccr4, Cxcr3, Ccl5, Cxcr5, Ccr1, Ccl2, Ccl4, and Ccr5 (Figure 3F). Moreover, we observed alterations in the gene signatures of both myeloid lineage markers and lymphoid lineage markers following NTN (Figure 3G-H).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the majority of cases in IS2 were MSS/MSI-L, which showed the lowest relative proportion of immune cells, which was potentially due to the low checkpoint-related gene expression levels. It has been reported that a high CCL4/CCL5/CXCL9/CXCL10 expression is strongly associated with CD8 + T-cell infiltration and T-cell activation (48)(49)(50)(51). Moreover, CXCL9, CXCL10, and CXCL11/CXCR3 axis play a central role in immune activation (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of anti-PD1 and anti-CSF1 receptor (CSF1R) antibodies induced the regression of melanoma in-driven transplanted mice ( Neubert et al, 2018 ). ITGB2 is associated with immune infiltration of multiple immune cell subsets, such as CD45, CD8, CD4T cells, CD20B cells and so on ( Kwak et al, 2021 ). Although there was no direct evidence for the association between TYROBP and melanoma, given the important association between these hub genes and immune infiltration, we regard them as potential therapeutic targets for patients with BRAF mutations.…”
Section: Discussionmentioning
confidence: 99%